Changes in expression of the long non-coding RNA FMR4 associate with altered gene expression during differentiation of human neural precursor cells - Peschansky, Veronica J.; Pastori, Chiara; Zeier, Zane; Motti, Dario; Wentzel, Katya; Velmeshev, Dmitry; Magistri, Marco; Bixby, John L.; Lemmon, Vance P.; Silva, José P.; Wahlestedt, Claes (Frontiers in Genetics, 2015)
CGG repeat expansions in the Fragile X mental retardation 1 (FMR1) gene are responsible for a family of associated disorders characterized by either intellectual disability and autism (Fragile X Syndrome, FXS), or adult-onset neurodegeneration (Fragile X-associated Tremor/Ataxia Syndrome, FXTAS). However, the FMR1 locus is complex and encodes several long noncoding RNAs (lncRNAs), whose expression is altered by repeat expansion mutations. The role of these lncRNAs is thus far unknown; therefore we investigated the functionality of FMR4, which we previously identified. “Full”-length expansions of the FMR1 triplet repeat cause silencing of both FMR1 and FMR4, thus we are interested in potential loss-of-function that may add to phenotypic manifestation of FXS. Since the two transcripts do not exhibit cis-regulation of one another, we examined the potential for FMR4 to regulate target genes at distal genomic loci using gene expression microarrays. We identified FMR4-responsive genes, including the methyl-CpG-binding domain protein 4 (MBD4). Furthermore, we found that in differentiating human neural precursor cells (hNPCs), FMR4 expression is developmentally regulated in opposition to expression of both FMR1 (which is expected to share a bidirectional promoter with FMR4) and MBD4. We therefore propose that FMR4’s function is as a gene-regulatory lncRNA and that this transcript may function in normal development. Closer examination of FMR4 increases our understanding of the role of regulatory lncRNA and the consequences of FMR1 repeat expansions.